Comparison of social results produced by Russian and foreign companies: case Russian electronic industry; Advances in Social Science, Education and Humanities Research; Vol. 28 : International Conference on Social Science and Higher Education: ICSSHE 2015, Sanya, China, December 26-27, 2015 - Spitsin V. V. Vladislav Vladimirovich; Tyuleneva N. A. Nataliya Aleksandrovna; Mikhalchuk A. A. Aleksandr Alexandrovich; Novoseltseva D. A. Darjya Andreevna; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Dyrina E. N. Evgeniya Nikolaevna (2015, 2015)
Title screen